ULUL ALBAB DALAM PANDANGAN MOCHAMAD SHOLEH Y.A.I DAN PENGEMBANGANNYA DI PERGURUAN MUHAMMADIYAH KOTTABARAT - Mohamad Ali; Mari Wulandari (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
Thoughts on the concept of Ulul Albab arose because of concerns that were born from a critical reading of the portrait of the reality of education, especially Islamic educationinIndonesia.TheUlulAlbabconceptgavebirthtoeducational innovation, namely the Sharia curriculum which can be seen from various perspectives. This research aims to describe the thoughts or concepts of Ulul Albab in the view of Prof. Mochamad Sholeh Y.A.I, Ph.D., and to describe how the development of the Ulul Albab concept Prof. Mochamad Sholeh Y.A.I, Ph.D. at the Muhammadiyah College of Kottabarat Surakarta. This research is a library qualitative research with a descriptive analysis method and uses a fhiloshopycal approach. This research is a type of library research with a descriptive type, which aims to describe reality or phenomena. In this study, the approach used is a historical and philosophical approach, which is used to examine the thoughts of a character and revealtheessenceofeverythingthatappears.Theresultsofthisstudyshow that the thoughts of Prof. Mochamad Sholeh Y.A.I, Ph.D. on (1) the concept of Islamic education Prof. Mochamad Sholeh Y.A.I, Ph.D. is the concept of Ulul Albab. (2) Development of the concept of Ulul Albab Prof. Mochamad Sholeh Y.A.I, Ph.D. at the Muhammadiyah College of Kottabarat Surakarta which is actualized in the form of a Sharia Curriculum both at the Muhammadiyah Elementary School for the Kottabarat Special Program, the MuhammadiyahJunior High School for the Kottabarat Special Program, and the Muhammadiyah High School for the Kottabarat Special Program.